Coca, cocaine, and the Bolivian reality - Léons, Madeline Barbara; Sanabria, Harry (State University of New York Press, 1997)
"Edited volume of contributions from Bolivian, American, and British political scientists, development sociologists, anthropologists, and historians examines impacts of the coca/cocaine economy on Bolivian society and politics, and on the US, in recent years. Together these works constitute the most complete, updated collection of analyses about this controversial public policy issue affecting US/Bolivian relations"--Handbook of Latin American Studies, v. 57.